Penerapan Metode Weighted Product dalam Sistem Pendukung Keputusan untuk Rekomendasi Tempat Gym Fitness Center Terbaik - M. Abdurozik; Witanti, Arita (Fakultas Teknik Universitas Hamzanwadi, 2025)
This study aims to design and develop a decision support system (DSS) based on the Weighted Product (WP) method to assist the public in selecting the best fitness center in Yogyakarta City. The wide range of available gyms, each offering varying facilities, pricing, services, and programs, presents a challenge for potential users in identifying options that align with their preferences. The proposed system utilizes five key criteria—facilities, membership fees, availability of personal trainers, distance, and user ratings—to generate objective recommendations. An initial trial conducted in Soropadan Village revealed that BlackBox Gym achieved the highest score of 0.040798, followed by The Fit Lab with a score of 0.03887 and Wzone Gym Studio – Jakal with a score of 0.036909. Further testing was performed across 30 sample points, each representing a sub-district within Yogyakarta City. The results indicated that MissFit Studio Gym ranked highest, achieving a preference score of 0.048897. The system demonstrated an accuracy rate of 97.56% when compared to manual calculations. These findings confirm that the application of the WP method is both effective and accurate in producing precise and consistent recommendations, thereby validating its reliability as a decision-making tool in selecting a fitness center.